2011
DOI: 10.1364/ol.36.002197
|View full text |Cite
|
Sign up to set email alerts
|

Fiber refractometer based on a fiber Bragg grating and single-mode–multimode–single-mode fiber structure

Abstract: A refractive index (RI) sensor based on a novel fiber structure which consists of a singlemode-multimodesinglemode (SMS) fiber structure followed by a fiber Bragg grating (FBG) was demonstrated. The multimode fiber (MMF) in the SMS structure excites cladding modes within output singlemode fiber (SMF) and re-couple the reflected cladding Bragg wavelength to the input SMF core. By measuring the relative Bragg wavelength shift between core and cladding Bragg wavelengths, the RI can be determined. Experimentally w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 127 publications
(52 citation statements)
references
References 17 publications
0
49
0
Order By: Relevance
“…When the SRI changes from 1.3350 to 1.4042RIU, the power of the core mode shifts about 12.81 dB, and the RI sensitivity is 193.55 dB/RIU, which is higher than TCF structure with FBG (133.26 dB/RIU) [11]. This is different from the MMFþ FBG fiber structure [8] in that the core mode keeps still with SRI changing. The reason for this is that we use MMFC here.…”
Section: Experiments and Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…When the SRI changes from 1.3350 to 1.4042RIU, the power of the core mode shifts about 12.81 dB, and the RI sensitivity is 193.55 dB/RIU, which is higher than TCF structure with FBG (133.26 dB/RIU) [11]. This is different from the MMFþ FBG fiber structure [8] in that the core mode keeps still with SRI changing. The reason for this is that we use MMFC here.…”
Section: Experiments and Discussionmentioning
confidence: 84%
“…By utilizing the coupling of the core mode and high-order modes [5,6], the RI sensitivity of the sensor is improved. The third is combination of FBG with other fiber structures to excite and couple the high-order mode [7,8]. In comparison with the former two techniques, FBG assisted with fiber structures have attracted attention for improving RI sensitivity without reducing the FBG strength and durability.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, when the refractive index of the external environment changes, the mode number M and the output spectral response will be changed accordingly [24]. Here, the Beam PROP simulation program (a part of the Rsoft Component Design Suite) was employed based on the beam propagation method (BPM).…”
Section: Theoretical Analysismentioning
confidence: 99%
“…So by measuring the relative Bragg wavelength shift between the core and the cladding Bragg wavelengths, the surrounding RI could be determined. (4,5) Yue Ma et al proposed a reflective refractometer based on a thin core (TCF) sandwiched between two single mode fibers followed by FBG. The reflection spectrum from this structure occurs at two well-defined wavelength bands, corresponding to the Bragg core mode and cladding modes.…”
Section: Introductionmentioning
confidence: 99%
“…(6) Gu et al experimentally demonstrated a reflective refractometer with high RI sensitivity based on a tilted FBG inscribed on a high photosensitive TCF by detecting changes in the cladding modes. (7) From above research, (4)(5)(6)(7)(8) it can be found that in addition to a core mode, cladding modes can also be coupled to the MZI by following it with an FBG, which will cause the MIZ spectrum to be modulated by the FBG. The characteristic of the FBG modulated MZI spectrum relate to the core mode, numerous cladding modes and reflection Bragg modes, among others.…”
Section: Introductionmentioning
confidence: 99%